2020
DOI: 10.22435/asp.v12i1.2765
|View full text |Cite
|
Sign up to set email alerts
|

Keragaman Spesies Vektor Japanese encephalitis di Sekitar Kandang Babi Kabupaten Tangerang

Abstract: Abstract. Japanese encephalitis is a mosquito-borne zoonotic disease that has pigs as the amplifying host. It is important to study the diversity of mosquito species around pig populations to determine the potential of Japanese encephalitis vectors in the region. This study is a cross-sectional study with a single sampling method for adult mosquitoes around pigpen in Tangerang Regency. The capture of adult mosquitoes is carried out by the outdoor resting mosquitoes collection at 18:00 - 24:00 using aspirators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The potential risk is also indicated by the location of several farms adjacent to residential areas. In line with the risk of mosquito breeding, our previous study also showed that the potential JEV mosquito vector has spread around pig farms in Tangerang District, with Culex vishnui and Culex quinquefasciatus as the dominant species [17]. Some of these Culex species have been reported as JEV vectors in Indonesia [5].…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…The potential risk is also indicated by the location of several farms adjacent to residential areas. In line with the risk of mosquito breeding, our previous study also showed that the potential JEV mosquito vector has spread around pig farms in Tangerang District, with Culex vishnui and Culex quinquefasciatus as the dominant species [17]. Some of these Culex species have been reported as JEV vectors in Indonesia [5].…”
Section: Discussionmentioning
confidence: 66%
“…The Subdistricts of Panongan, Tigaraksa, and Solear are close to each other and belong to rural areas. Based on the results of our previous study, it was shown that the environmental characteristics of almost all pig and cattle farms were found stagnant water and close to paddy fields [17]. This shows the existence of a risk factor for JEV transmission, i.e.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations